Organization of the mammalian ionome according to organ origin, lineage specialization and longevity - Ma, Siming (Cell Rep, 2015)
Trace elements are essential to all mammals, but their distribution and utilization across species and organs remains unclear. Here we examined 18 elements in the brain, heart, kidney, and liver of 26 mammalian species, and report the elemental composition of these organs, the patterns of utilization across the species, and their correlation with body mass and longevity. Across the organs we observed distinct distribution patterns for abundant elements, transition metals, and toxic elements. Some elements showed lineage-specific patterns, including reduced selenium utilization in African mole rats, and positive correlation between the number of selenocysteine residues in selenoprotein P and the selenium levels in liver and kidney across mammals. Body mass was linked positively to zinc levels, whereas species lifespan correlated positively with cadmium and negatively with selenium. This study provides insights into the variation of mammalian ionome by organ physiology, lineage specialization, body mass, and longevity.